To begin again artists and childhood - De Blois, Jeffrey; Erickson, Ruth (DelMonico Books, D.A.P., 2022)
"To Begin Again: Artists and Childhood surveys how artists have reflected on and contributed to notions of childhood from the early 20th century to the present. The works offer distinctive viewpoints and experiences, revealing how time and place, economics and race, and representation and aesthetics fundamentally shape how we experience and understand early development. The catalog underscores that while there is no single, uniform idea of childhood, it is nevertheless the ground upon which so much of society is built, negotiated, and imagined" -- publisher's description
Impressum: This book is published on the occasion of "To Begin Again: Artists and Childhood", October 6, 2022 - February 26, 2023
Includes interviews with Naima J. Keith, Oscar Murillo, Sable Elyse Smith, Mierle Laderman Ukeles, and Carmen Winant
Artists include: Ann Agee, John Ahearn, Njideka Akunyili Crosby, Francis Alÿs, Jean-Michel Basquiat, Brian Belott, Jordan Casteel, Lenka Clayton, Allan Rohan Crite, Henry Darger, Karon Davis, Robert Gober, Jay Lynn Gomez, Trenton Doyle Hancock, Duane Hanson, Mona Hatoum, Sharon Hayes, Ekua Holmes, Mary Kelly, Paul Klee, Justine Kurland, Helen Levitt, Tau Lewis, Glenn Ligon, Oscar Murillo, Rivane Neuenschwander, Berenice Olmedo, Charles Ray, Faith Ringgold, Deborah Roberts, Tim Rollins and K.O.S., Rachel Rose, Heji Shin, Sable Elyse Smith, Becky Suss, Mierle Laderman Ukeles, Cathy Wilkes and Carmen Winant
Keywords: Geschichte 1880-2022; Kunst; Kind -- Motiv; Children in art / Exhibitions; Exhibition catalogs; Ausstellungskatalog -- Institute of Contemporary Art -- 06.10.2022-26.02.2023 -- Boston, Mass.